Mutational analysis of HIV‐2 Vpx shows that proline residue 109 in the poly‐proline motif regulates degradation of SAMHD1. Issue 13 (30th April 2015) - Ciftci, Halil Ibrahim; Fujino, Haruna; Koga, Ryoko; Yamamoto, Minami; Kawamura, Sogo; Tateishi, Hiroshi; Iwatani, Yasumasa; Otsuka, Masami; Fujita, Mikako
Abstract : In this study, we performed a mutational analysis to determine whether the mechanism by which HIV‐2 Vpx confers the capacity for infectivity and viral replication in macrophages is solely dependent on its ability to degrade the host antiviral factor SAMHD1. Contrary to expectations, we demonstrated that P 109 in the C‐terminal poly‐proline motif of HIV‐2 Vpx has two unique roles: to facilitate the specific degradation of SAMHD1 in macrophages, and to facilitate multimerization of Vpx, therefore preventing SAMHD1 degradation in the presence of high levels of Vpx. Abstract : We performed a mutational analysis of HIV‐2 Vpx activity. P 109 in the C‐terminal poly‐proline motif of HIV‐2 Vpx has multiple functions. P 109 is required for efficient degradation of SAMHD1 specifically in macrophages. P 109 is required for multimerization of Vpx. P 109 prevents SAMHD1 degradation in the presence of high levels of Vpx.